The neurostructural bases of empathy: morphometric evidence for a multicomponential approach - Arioli, Maria; Rassouli Baghi, Leonardo; Cattaneo, Zaira; Canessa, Nicola (Frontiers in Psychiatry, 2025)
The neural bases of individual differences in empathy subcomponents are still debated. We employed brain morphometry to investigate the neurostructural bases of individual and sex differences in specific empathy facets in 124 healthy individuals who completed the Balanced-Emotional-Empathy-Scale (BEES), and both the emotional/cognitive and self/other-oriented empathy subscales of the Interpersonal-Reactivity-Index (IRI). Univariate and multivariate morphometric analyses highlighted, respectively, voxels/clusters and whole structural networks where grey-matter volume reflected specific empathy subscores. Such morphometric properties were significantly related to individual differences in emotional empathy, while no evidence was found for structural networks underlying cognitive empathy. Personal distress correlated with grey-matter volume in the right insula and amygdala, likely mediating an affective sharing self-perceived as disturbing. Instead, empathic concern was associated with the medial precuneus and sensorimotor/inferior parietal cortex, possibly enabling empathic comprehension and prosocial behaviour mediated by attentional shift towards others. Female participants displayed larger grey-matter volume than male ones, related to higher emotional empathy, in limbic structures including amygdala and insula. These results ground multicomponential empathy models in specific neurostructural networks, representing a reference for future studies of empathic processing in health and disease.